Steady, Dynamic, Creep, and Recovery Analysis of Ice Cream Mixes Added with Different Concentrations of Xanthan Gum - Dogan, Mahmut; Kayacier, Ahmed; Toker, Omer Said; Yilmaz, Mustafa Tahsin; Karaman, Safa (SPRINGER, 2013)
Different xanthan gum concentrations (0-0.8 %) were tested, and the rheological properties of ice cream mixes were characterized as linear viscoelastic solids. Ostwald de Waele was successfully used to fit the steady shear data of ice cream mixes exhibiting a pseudoplastic flow (R (2) > 0.982). The samples with xanthan gum were characterized as strong gel-like macromolecular dispersions with G' much greater than GaEuro(3) but without a cross-point in the whole range of frequency applied. Cox-Merz rule was not applicable to the ice cream mixes. Steady and dynamic rheology of the ice cream mixes changed with increasing xanthan gum concentration. Besides, the four-component Burger model consisted of the association in series of the Maxwell model and the Kelvin-Voigt model was used to characterize the viscoelasticity. It was also found that the final percentage recovery parameters; J (SM), J (a), J (KV), and %R (compliance of Maxwell spring and dashpot, Kelvin-Voigt element and R, respectively) of the ice cream mixes were dramatically changed by the xanthan gum concentration, increasing the internal structure parameters G (0), G (1), eta (0), and eta (1) (elastic moduli of Maxwell and Kelvin-Voigt springs and corresponding dashpot viscosities, respectively).
Keywords: Ice cream; Xanthan gum; Steady shear; Dynamic shear; Creep and recovery test; RHEOLOGICAL PROPERTIES; VISCOELASTIC PROPERTIES; FLOW BEHAVIOR; WATER; TEXTURE; WHEY; HYDROCOLLOIDS; TEMPERATURE; QUALITY; SYSTEMS; Food Science & Technology